Construction of an improved D-arabinose pathway in Escherichia coli K-12. - Bartkus, J M (1986)
A ribitol catabolic pathway was transduced into Escherichia coli K-12 in an effort to determine whether the ribitol pathway would confer an advantage to D-arabinose-positive mutants growing on D-arabinose as the sole carbon source. Competition studies in chemostats showed that ribitol-positive strains, with a selection coefficient of 9%/h, have a significant competitive advantage over ribitol-negative strains. Ribitol-positive strains grown in batch culture also exhibited a shorter lag period than did ribitol-negative strains when transferred from glucose to D-arabinose. Repeated transfer of a ribitol-positive strain of E. coli K-12 on D-arabinose yielded a strain with further improved growth on D-arabinose. This "evolved" strain was found to constitutively synthesize L-fucose permease, isomerase, and kinase but had lost the ability to grow on L-fucose, apparently owing to the loss of a functional aldolase. This constitutive mutation is not linked to the fucose gene cluster and may be similar to an unlinked constitutive mutation described by Chen et al. (J. Bacteriol. 159:725-729, 1984).